Voice as Action: Towards a Model for Analyzing the Dynamic Construction of Racialized Voice - Eidsheim, Nina (Current Musicology, 2012)
Vocal timbre is commonly believed to be an unmanipulable attribute, akin to a sonic fingerprint. Because the voice arises from inside the body, quotidian discourse tends to refer to someone’s vocal sounds as inborn, natural, and true expressions of the person. What, then, are we to make of the common notion that a person’s race is audible in her voice? While it has been conclusively demonstrated that many of the physiognomic aspects historically employed as evidence of a person’s race—including skin color, hair texture, and dialect or accent —actually evidence nothing more than the construction of race according to the ideological values of beholders, vocal timbre continues to elude such deconstruction. Recent critical thought on the intermingling of the physical senses, including the so–called sensory turn in anthropology, “new materialist” philosophies, and recent advances in science, technology, sound studies, and media studies, underscores the need for scholarship that recognizes the voice and vocal categories as culturally conditioned material entities. Trends such as the metaphorical notion of “having voice” have to some degree obscured the material and multisensory aspects of voice. Conceived within the specific context of musicology and the general context of the humanities, this article seeks to demonstrate how the re–framing of voice implied by sensory and material inquiries redraws the topology of voice. I believe that this exercise may offer a deepened understanding of racial dynamics as they play out in our interactions with voice.